Antimicrobial supplementation alters digestibility and ruminal fermentation in a continuous culture model. Issue 1 (1st January 2021) - Thompson, Alex J.; Smith, Zachary K.; Sarturi, Jhones O.; Johnson, Bradley J.
ABSTRACT: A dual-flow continuous culture system was used to evaluate the effects of laidlomycin propionate and bacitracin zinc on fermentation, nutrient digestibility, and microbial efficiency. Factors were laidlomycin propionate (LP ; 2 mg/L of culture volume) and bacitracin zinc (BAC ; 1.4 mg/L), and treatments were as follows: (1) no BAC or LP (CON ), (2) LP without BAC (LP ), (3) BAC without LP (BAC ), and (4) LP and BAC (LP/BAC ). A fifth treatment was supplemented with monensin sodium (MON ; 6 mg/L) to act as a positive control. Both LP and LP/BAC had significantly greater pH than MON ( P  < 0.05). Antibiotic treatment did not affect NH 3 -N concentration ( P  = 0.62), but did influence total VFA production ( P  = 0.02). Monensin fermenters had a greater proportion of total VFA than did LP fermenters ( P  < 0.05), and improved VFA production by 7.2% compared to CON. Laidlomycin suppressed the production of both acetate ( P  < 0.01) and butyrate ( P  = 0.05), and acetate was further reduced when LP was fed in combination with BAC ( P  = 0.01). Laidlomycin numerically reduced the acetate:propionate ratio ( P  = 0.12). These results suggest that bacitracin may produce ionophore-like effects on pH and VFA production in vitro .